Subacute pericardial abscess after aortic valve replacement: a case report - Ilenia Magnani; Alberto Spadotto; Pasquale Paolisso; Alberto Foà; Carlo Savini; Davide Pacini; Carmine Pizzi; Nazzareno Galiè (BMC Infectious Diseases, 2020)
Abstract Background Purulent pericarditis is an infectious disease, frequently caused by gram-positive bacteria, that is rarely observed in healthy individuals, and is often associated with predisposing conditions. Case presentation Here, we present the case of an Escherichia coli post-surgical localized purulent pericarditis complicated by transient constrictive pericarditis and its diagnostic and therapeutic management. Conclusions Our case report focuses on the importance of imaging-guided treatment of purulent pericardial diseases, in particular on the emerging role of 18 F-labelled 2-fluoro-2-deoxy-D-glucose Positron Emission Tomography/Computed Tomography in pericardial diseases and on the management of transient constrictive pericarditis, often seen after thoracic surgery.